Regulación hormonal del grado de sialización de la FSH y su posible implicancia fisiológica - Ambao, Verónica Ana (2016)
FSH is produced and secreted as a family of glycosylation variants which differ from\neach other in the sialylation and complexity degree of its oligosaccharides and in the\ninduction of biological responses. El objetivo general de esta Tesis Doctoral fue\ndeterminar la regulación hormonal y el mecanismo por el cual se producen cambios en\nel grado de sialización de la molécula de FSH y su posible implicancia sobre la\nregulación de la función testicular.\nThe aim of this Doctoral Thesis was to determine the mechanisms involved in the\nhormonal regulation of FSH sialylation and the impact of this characteristic on the\ntesticular function. Alterations in serum FSH sialylation, in GnRH and in androgen\nactions were observed in anorquid patients. An increment in FSH sialylation was\nobserved during sexual development in the rat. Castration, androgens and GnRH\nantagonist affected FSH glycosylation and the gene expression of St6gal1. Different\ncharge analogues isolated from FSHrh induced differential responses on the estradiol,\ncAMP and inhibins production by immature Sertoli cells.\nThese results show that the regulation of sialyltransferases gene expression, FSH\nsialylation degree ? involved in the differential response of the target cell ? require the\nfunctional integrity of the hypothalamic?pituitary?testicular axis.